Board Game in The Learning of Academic English Writing - Joseph, Ramanair; Soubakeavathi, Rethinasamy; Damien, Mikeng; Ashley E.R., Soosay; Jecky, Misieng (CALM, UNIMAS, 2020)
Making connections between learning and teaching in the classroom is crucial as it empowers learners to realise the purpose of education as a whole. It enables learners to put their learning into perspective, stimulate them to master the required skills and knowledge in a thoughtful manner, and encourages them to interact, collaborate and cooperate so as to learn from one another. Classroom teaching approaches thus, need to facilitate learners to learn by helping them to make connections in their learning. Making such connections is also important in an increasingly interconnected world of the 21st century particularly as the future of learning as envisioned in Education 4.0, is built around shared knowledge and aspiration